The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/jcm7020035
|View full text |Cite
|
Sign up to set email alerts
|

From Prenatal to Preimplantation Genetic Diagnosis of β-Thalassemia. Prevention Model in 8748 Cases: 40 Years of Single Center Experience

Abstract: The incidence of β-thalassemia in Sardinia is high and β-39 is the most common mutation. The prevention campaign started in 1977 and was performed in a single center (Microcitemico Hospital, Cagliari, Sardinia, Italy). It was based on educational programs, population screening by hematological and molecular identification of the carriers. Prenatal and pre-implantation diagnosis was offered to couples at risk. 8564 fetal diagnosis procedures using different invasive approaches and analysis techniques were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 65 publications
0
29
0
1
Order By: Relevance
“…59,60 Free voluntary carrier screening as well as prenatal and preimplantation genetic diagnostics are available nationwide. 57,60 Increasing awareness among the general population, leading to acceptance of screening, has been a major success factor of the Italian prevention program. 32,60 In a report covering 40 years of experience with a screening program in Sardinia, the main causes of affected births (3-5 annually in recent years) were false paternity and decline of prenatal screening and pregnancy termination.…”
Section: Prevention Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…59,60 Free voluntary carrier screening as well as prenatal and preimplantation genetic diagnostics are available nationwide. 57,60 Increasing awareness among the general population, leading to acceptance of screening, has been a major success factor of the Italian prevention program. 32,60 In a report covering 40 years of experience with a screening program in Sardinia, the main causes of affected births (3-5 annually in recent years) were false paternity and decline of prenatal screening and pregnancy termination.…”
Section: Prevention Programsmentioning
confidence: 99%
“…57,60 Increasing awareness among the general population, leading to acceptance of screening, has been a major success factor of the Italian prevention program. 32,60 In a report covering 40 years of experience with a screening program in Sardinia, the main causes of affected births (3-5 annually in recent years) were false paternity and decline of prenatal screening and pregnancy termination. 59,60 In Sicily, an 85% decrease in the in- counseling, and prenatal diagnosis.…”
Section: Prevention Programsmentioning
confidence: 99%
“…It is believed that codon 39 (C> T) is of Roman origin, and has a high prevalence in Sardinia, mainland Italy, Spain, Portugal and Tunisia (19). Different studies also found this mutation to be frequent in Venezuela (18), Northern Greece (20), Syria (21), and confirmed it in Tunisia (22) and Italy (23).…”
mentioning
confidence: 74%
“…The prevention and control of thalassemias in any national program require a planned program and consultations with all the major stakeholders to establish the various components needed to ensure its success. The program must include an education component for the professionals and public, optimal treatment of the affected patient including safe blood transfusion and iron chelation therapy, cascade screening of the family and population‐wide screening, a registry to provide epidemiological data and a preventive program that may include genetic counseling, prenatal diagnosis and preimplantation genetic diagnosis (Monni, Peddes, Iuculano, & Ibba, ). This holistic approach is cost‐effective and had proven to be successful in reducing the frequency of thalassaemia in many countries such as Cyprus and Greece (Kyrri et al, ; Ladis, Karagiorga‐Lagana, Tsatra, & Chouliaras, ).…”
Section: Prevention and Control Of Thalassemia In The Asian Regionmentioning
confidence: 99%